The role of CDKs in co-transcriptional splicing through phosphorylation of the RNA Pol II carboxy-terminal domain (CTD) - Cunha, Thais Souza (2022)
Tese de mestrado, Ciências Biofarmacêuticas, 2021, Universidade de Lisboa, Faculdade de Farmácia.